How to monitor the brain in COVID-19 patients?. (April 2021) - Peluso, Lorenzo; Minini, Andrea; Taccone, Fabio Silvio
Highlights: Due to the high occurrence of brain complications during COVID-19, monitoring of cerebral functions is necessary. Clinical examination should be routinely performed in all patients and used to decide for neuro-imaging, whenever necessary. In heavily sedated or paralyzed patients (i.e. unreliable clinical examination), non-invasive neuromonitoring could provide additional information on cerebral function of these patients. In daily practice, trained nurses could obtain relevant findings from cerebral ultrasound, cerebral near-infrared spectroscopy, quantified EEG and automated pupillometry to assess cerebral function in COVID-19 critically ill patients